Sulfamethoxazole and Enrofloxacin Antibiotics Affect Primary Productivity of Phytoplankton in Fishery Environment - Shan, Xiangbao; Shi, Yulu; Fang, Longxiang; Gui, Yuan; Xing, Luchang; Qiu, Liping; Hu, Gengdong; Chen, Jiazhang (Frontiers in Environmental Science, 2021)
The antibiotics sulfamethoxazole (SMZ) and enrofloxacin (ENF) are commonly used in aquaculture in China, but their effects on the primary productivity of phytoplankton are unclear. On the basis of the fishery drug use standards (SMZ, 100 mg·kg−1·d−1; ENF, 15 mg·kg−1·d−1), these antibiotics were put into culture ponds to observe their effects on the phytoplankton community and primary productivity. The results showed that the changes in phytoplankton species at SMZ and ENF sites were different. At the ENF sites, Bacillariophyta species increased from 7 to 9, euglenophyta from 8 to 12 and cyanophyta from 11 to 9. Chlorophyta species at the SMZ sites increased from 10 to 15 and euglenophyta from 7 to 4. SMZ and ENF significantly promoted the number of cyanophyta (P < 0.05). The promoting effect of SMZ was more obvious than that of ENF. SMZ was more effective than ENF in promoting cyanophyta. The maximum number of cyanophyta at SMZ sites was 52.39 million·L−1, and the concentration of SMZ was positively correlated with the number of cyanophyta. The maximum number of cyanophyta at ENF sites was 33.13 million·L−1, and the promoting effect of low concentrations was more significant than that of high concentrations. Both SMZ and ENF promoted increased phytoplankton biomass, consistent with the residual time of the antibiotics in the aquaculture environment. The greatest biomass at the SMZ sites was 129.31 g·m−³, and that at the ENF sites was 117.85 g·m−³. The changes in the α diversity index showed that both SMZ and ENF led to a decrease in phytoplankton biodiversity, and that SMZ was more harmful to it. There were significant differences in the Shannon–Wiener, Pielou and Simpson indexes of the SMZ sites among groups (P < 0.05). The β diversity index showed that both antibiotics could change the phytoplankton habitat, but the effect of ENF on the habitat was recoverable, while that of SMZ prevented its restoration. These data will be valuable in protecting the ecological environment of fisheries and in ensuring the safety and stability of fishery aquatic ecosystems.